2022
DOI: 10.1007/978-3-030-95459-8_45
|View full text |Cite
|
Sign up to set email alerts
|

Visual-Inertial Localization for Skid-Steering Robots with Kinematic Constraints

Abstract: While visual localization or SLAM has witnessed great progress in past decades, when deploying it on a mobile robot in practice, few works have explicitly considered the kinematic (or dynamic) constraints of the real robotic system when designing state estimators. To promote the practical deployment of current state-of-the-art visual-inertial localization algorithms, in this work we propose a low-cost kinematics-constrained localization system particularly for a skid-steering mobile robot. In particular, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Alternatively, observability properties can also be directly analyzed under continuous-time nonlinear format, and a representative family of methods is to compute continuous-time observability matrices via selecting proper equations of Lie derivatives (Guo and Roumeliotis, 2013;Yang and Huang, 2019). Another category of widely used tools for observability analysis is to directly investigate the sensors' measurement models and robot's kinematic equations, to identify whether there exist sets of different states that are able to generate identical sensor measurements under the same system inputs, following the definition of observability (Jones and Soatto, 2011;Censi et al, 2013;Li and Mourikis, 2014b;Zuo et al, 2019b).…”
Section: Observability Analysis For Localization Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, observability properties can also be directly analyzed under continuous-time nonlinear format, and a representative family of methods is to compute continuous-time observability matrices via selecting proper equations of Lie derivatives (Guo and Roumeliotis, 2013;Yang and Huang, 2019). Another category of widely used tools for observability analysis is to directly investigate the sensors' measurement models and robot's kinematic equations, to identify whether there exist sets of different states that are able to generate identical sensor measurements under the same system inputs, following the definition of observability (Jones and Soatto, 2011;Censi et al, 2013;Li and Mourikis, 2014b;Zuo et al, 2019b).…”
Section: Observability Analysis For Localization Algorithmsmentioning
confidence: 99%
“…Our previous work (Zuo et al, 2019b)) performed observability analysis of localizing steering skid robot by using a monocular camera, wheel encoders, and an IMU, and showed that the skid-steering parameters are generally observable. In this work, we significantly extend the analysis in (Zuo et al, 2019b), by explicitly identifying the identifiable and nonidentifiable parameters with and without using the IMU.…”
Section: Observability Analysis For Localization Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, non-holonomic constraints of vehicles have proven valuable in improving estimation accuracy [27]. Zuo et al derived kinematic constraints of vehicles using the instantaneous center of rotation and seamlessly integrated this information into a visual-inertial estimator, yielding superior results compared to conventional VIO systems [28]. Expanding on this work, Huang enhanced the robustness of odometry systems by incorporating non-holonomic constraints specific to vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, constant approximations of tread ICR values for flat terrain under low inertia can be identified with offline experiments [16] [21] or online during navigation [22]. ICR kinematics has been employed as the basis for path tracking [23], for online power consumption estimation [24], for dynamic modeling [25], for online terrain classification [26] and, also, as constraints for simultaneous localization and mapping [27].…”
Section: Introductionmentioning
confidence: 99%